UNSTABLE LUMBAR FRACTURE-DISLOCATION TREATED BY LONG SEGMENT POSTERIOR PEDICLE SCREW INSTRUMENTATION - Ferdiansyah Danang; Primadenny Ariesa Airlangga (Journal Orthopaedi and Traumatology Surabaya)
Background: Among all the thoracolumbar fractures, 50-60% affects the thoracolumbar transitional zone, and 51% AO Type C Fractures has a neurological deficit. We experienced treating a case of unstable lumbar fracture-dislocation treated with long segment pedicle screw instrumentation.